Family violence and abuse an encyclopedia of trends, issues, and solutions - Salari, Sonia (Bloomsbury Academic, 2024)
"Surveys family violence and abuse in America and the many forms that it can take. Provides extensive coverage of widely recognized forms of violence and abuse in family settings, including physical, verbal, and emotional abuse of spouses and intimate partners female as well as children"--